KOMUNIKASI KRISIS PADA PT. DARMA KALIMANTAN JAYA (STUDI KASUS TENTANG KONFLIK PENGELOLAAN LIMBAH PABRIK) - Firdaus, Rahmat; Fathurrahman; Ayuni, Risa Dwi (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
This study aims to explore how crisis communication strategies were implemented by PT. Darma Kalimantan Jaya in addressing the conflict over industrial waste management, as well as to analyze the effectiveness of the conflict resolution process in rebuilding public trust. The research adopts a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation involving five key informants consisting of company representatives, community leaders, and affected residents. Informants were selected using purposive sampling, while data were analyzed using thematic and narrative approaches to identify communication patterns and the dynamics of the crisis. The results reveal that in the early stages of the crisis, the company’s communication was closed, defensive, and reactive, which worsened its relationship with the surrounding community. However, under public and media pressure, the company initiated significant changes by forming a crisis communication team, conducting open meetings with local residents, and implementing corrective actions such as improving waste treatment systems and enhancing information transparency. These measures gradually reduced the intensity of the conflict, helped restore the company’s image, and rebuilt community trust. This study concludes that the effectiveness of crisis communication depends not only on the speed and accuracy of the response but also on information transparency, empathy toward affected communities, and public participation in the conflict resolution process. Theoretically, this research contributes to strengthening a community-based crisis communication model within the rubber industry context and serves as a reference for other industrial companies in managing environmental crises ethically, transparently, and sustainably.   Keyword; Crisis Communication, Waste Management, Conflict Resolution, Information Transparency, PT. Darma Kalimantan Jaya.